2021
DOI: 10.3389/fmicb.2021.761583
|View full text |Cite
|
Sign up to set email alerts
|

A New pH-Responsive Nano Micelle for Enhancing the Effect of a Hydrophobic Bactericidal Agent on Mature Streptococcus mutans Biofilm

Abstract: The bactericidal effect on biofilm is the main challenge currently faced by antibacterial agents. Nanoscale drug-delivery materials can enhance biofilm penetrability and drug bioavailability, and have significant applications in the biomedical field. Dental caries is a typical biofilm-related disease, and the acidification of biofilm pH is closely related to the development of dental caries. In this study, a pH-responsive core-shell nano micelle (mPEG-b-PDPA) capable of loading hydrophobic antibacterial agents… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(25 citation statements)
references
References 45 publications
1
24
0
Order By: Relevance
“…In-vivo experiments showed that farnesol reduced the severity of smooth and sulcal surface caries in rats infected with S. mutans [ 89 ]. Similar results were observed in pH-responsive micelles fabricated with methoxypolyethylene glycol-b-poly-2-(diisopropylamino) ethyl methacrylate (mPEG-b-PDPA) loaded with bedaquiline [ 184 ]. Antimicrobial fillers have also been encapsulated into these pH-responsive carriers.…”
Section: Smart Dental Materials For Antimicrobial and Antibiofilm The...supporting
confidence: 72%
See 1 more Smart Citation
“…In-vivo experiments showed that farnesol reduced the severity of smooth and sulcal surface caries in rats infected with S. mutans [ 89 ]. Similar results were observed in pH-responsive micelles fabricated with methoxypolyethylene glycol-b-poly-2-(diisopropylamino) ethyl methacrylate (mPEG-b-PDPA) loaded with bedaquiline [ 184 ]. Antimicrobial fillers have also been encapsulated into these pH-responsive carriers.…”
Section: Smart Dental Materials For Antimicrobial and Antibiofilm The...supporting
confidence: 72%
“…pH-responsive nanocarriers protect the encapsulated agent from degradation and can release their cargo in a controlled manner. Additionally, the localized release of the agent increases therapy efficacy due to increased penetration within biofilms and improved agent stability and solubility [ 184 ]. For example, pH-responsive micelles are used to encapsulate and release farnesol for caries treatment [ 89 ].…”
Section: Smart Dental Materials For Antimicrobial and Antibiofilm The...mentioning
confidence: 99%
“…A growing problem of modern society is related to the uncontrolled use of antibiotics which have as a consequence increased multimicrobial resistance, affecting thus the global health system. An extremely sophisticated microbial environment is located in the oral cavity, in which can be found around 700 strains that can contribute to the rapid development of oral diseases [ 17 ]. Even if the synthesis of new drugs with antimicrobial activity has recorded remarkable progress in the last few years, their low solubility and bioavailability, high toxicity and inadequate release profile limits their clinical utilization [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…An antibacterial agent, bedaquiline, exhibits high effects on killing planktonic bacteria but have limited efficacy in removing mature biofilm (Flemming et al, 2016;Bowen et al, 2018;Zhang et al, 2021). In order to improve permeability of bedaquiline to mature biofilm, Zhang et al synthesized a novel pH-activated nano micelle, core-shell nano micelle (mPEG-b-PDPA), for loading hydrophobic antibacterial agents (Zhang et al, 2021). The release rate of bedaquiline was very gentle at pH 7, with about 35% in the first 12 h, while the amount released within 3 h reached 92.2% at pH 5.…”
Section: Ph-responsive Charge And/or Hydrophilicity Shifting Systemsmentioning
confidence: 99%